HPLC ANALYSIS AND ANTIFUNGAL ACTIVITY OF SOME PLANT EXTRACTS AGAINST DECAY APPLE FRUITS - A. A. YOUSIF; W. A. HASSAN (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to determine the qualitative and quantitative phenolic compounds. Results revealed that HPLC analysis identified Hydroxy derivatives of benzoic acids, hydroxy-cinnamic acids, in addition to flavonoids. The major compounds detected in clove were eugenol 32.5 mg/L, while in thyme the predominant phenol was gallic acid 35.9 mg/L. Quercetin was the greatest phenolic compound in both eucalyptus and sage 49.8 and 55.6 mg/L, respectively. Clove extract inhibited all selected pathogens entirely when applied at 20%. Subsequently, thyme extract at the same concentration inhibited the growth of B. cinerea completely. Eucalyptus extract revealed a lowest inhibition with 23.2%, 11.83%, and 7.83% after three, six, and nine days, respectively. P. griseofulvum showed remarkable susceptibility to extracts due to 51.99% growth inhibition followed by 25.33% and 20.67% for both A. alternata and B. cinerea, respectively.